FULFILLMENT OF GOOD FAITH PRINCIPLE IN PREPARATION OF STANDARD CLAUSES - Celina Tri Siwi Kristiyanti (NOTARIIL Jurnal Kenotariatan, 2019)
Standard clauses are made by business actors with the aim of efficiency and effectiveness. However, various problems arise from standard clauses made by business actors both producing goods and providing services. Standard clause is not prohibited if it pays attention to the balanced position of the parties, but conversely if it contains exoneration clause then this is categorized as null and void. Provisions on the prohibited standard clause are regulated in Law No. 8 of 1999 concerning Consumer Protection of Article 18. This study aims to determine the fulfillment of good faith principles in the preparation of standard clauses and identify the consequences of the agreement containing standard clauses that are not in accordance with the principles of good faith. The research method used is normative research using primary legal material from the Civil Code, Law No. 8 of 1999 concerning Consumer Protection and secondary legal materials in the form of reference books and articles in legal journals. The results obtained, the principle of good faith is regulated in Book III of KUHPdt article 1338 thus it must be concretized in the form of an agreement with a standard clause that provides a balanced position for the parties. If there is an exoneration clause, the standard agreement is categorized as null and void.